2003
DOI: 10.1152/ajpcell.00077.2003
|View full text |Cite
|
Sign up to set email alerts
|

Channels formed with a mutant prion protein PrP(82-146) homologous to a 7-kDa fragment in diseased brain of GSS patients

Abstract: A major prion protein (PrP) mutant that forms amyloid fibrils in the diseased brain of patients with Gerstmann-Sträussler-Scheinker syndrome (GSS) is a fragment of 7 kDa spanning from residues 81-82 to 144-153 of PrP. Analysis of ionic membrane currents, recorded with a lipid bilayer technique, revealed that the wild-type fragment PrP(82-146) WT and the partially scrambled PrP(82-146) (127-146) SC are capable of forming heterogeneous ion channels that are similar to those channels formed with PrP(106-126). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…For instance, amyloidogenic peptides share a common mechanism of toxicity based on membrane destabilization and the formation of ion-permeable pores (Demuro et al, 2005). We found that both wild-type and partially scrambled PrP 82-146 peptides form ion channels in artificial membranes (Bahadi et al, 2003) and alter the membrane fluidity . In addition, the squalene synthase inhibitor squalestatin, which reduces plasma membrane cholesterol, antagonized the toxic effect of PrP 82-146 (Bate et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…For instance, amyloidogenic peptides share a common mechanism of toxicity based on membrane destabilization and the formation of ion-permeable pores (Demuro et al, 2005). We found that both wild-type and partially scrambled PrP 82-146 peptides form ion channels in artificial membranes (Bahadi et al, 2003) and alter the membrane fluidity . In addition, the squalene synthase inhibitor squalestatin, which reduces plasma membrane cholesterol, antagonized the toxic effect of PrP 82-146 (Bate et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…A much larger segment of the prion protein was later shown to form pores, PrP 82 to 145, which is the peptide found in the amyloid in the brains of patients with Gerstmann-Straussler-Scheinker syndrome, but the 106-126 sequence was essential to pore formation. 63 The PrP 106-126 pores can be inhibited by preincubation with Congo red indicating that they must be in beta sheet structure to aggregate and form pores. Zinc ion is capable of reversibly blocking these pores after they have formed.…”
Section: Prion Peptidesmentioning
confidence: 99%
“…13 Interestingly, PrP82-146 was found to interact with biological membranes 13 and to form ion channels in lipid bilayers. 14 For these reasons, the human PrP82-146 peptide has been used as a model system to investigate the peculiar features of amyloid polymerization, 15 the anti-prionic properties of tetracyclines, 16 and the role of metal ions in fibrillogenesis. 17 Interestingly, PrP82-146 oligomers were found to have biological activities triggering neuron cell death and activating a gliotrophic response.…”
Section: Introductionmentioning
confidence: 99%